The thread of space, time and event: An implication in media studies - Poudel, Krishna (Bodhi: An Interdisciplinary Journal, 2010)
Recently widely circulated publications, the World Development Report 2009 of the World Bank (WB) and Human Development Report 2007/2008 of the United Nations Development Programmes (UNDP), have strongly emphasized the geographical space of the world. The World Development Report 2009 has a sub-title ‘reshaping the economic geography', whereas the Human Development Report has dealt on ‘fighting climate change, human solidarity in a divided world'. Both these documents have tried to disseminate a clear message about the interrelationship of geographical space and the human and natural processes, with special reference to functions and events associated in the contemporary world. The space is usually characterized by its elements of dimensionality, continuity, proximity and separation (NRC, 2006). Dimensions are components of a coordinate grid typically used to locate a point, line or area in a certain defined ‘space' as, for example, on the globe by latitude, longitude and elevation (X, Y and Z). In space-time, a coordinate grid that spans the 3+1 dimensions locates ‘events' (rather than just points in space), so time is added as another dimension to the grid, and another axis. This way, it is possible to plot where and when something is. Unlike in normal spatial coordinates, there are restrictions for how measurements can be made spatially and temporally. This is closely associated with the representation of events in the contextual ground of space and time. The representations can be made in a variety of modes and media (graphic [text, image or maps, and video], tactile, auditory, kinesthetic, and olfactory) to describe, explain, and communicate about the structure, operation, and function of objects and their relationships. Spatial thinking is not restricted to any domain of knowledge (NRC 2006). DOI: 10.3126/bodhi.v3i1.2815 Bodhi Vol.3(1) 2009 p.92-98